A single fibril study reveals that ApoE inhibits the elongation of Aβ42 fibrils in an isoform-dependent manner - Sourav Dasadhikari; Shamasree Ghosh; Sudip Pal; Tuomas P. J. Knowles; Kanchan Garai (Communications Chemistry)
Abstract ApoE-ε4 is the strongest genetic risk factor for late-onset Alzheimer’s disease (AD), linked to increased amyloid-β (Aβ) deposition in the brain. In AD mouse models, microglial expression of apoE3 reduces amyloid plaque burden through enhanced phagocytosis, whereas apoE4 is associated with impaired Aβ clearance. However, the isoform-specific interactions of apoE with Aβ aggregates and the molecular mechanisms by which these isoforms influence Aβ aggregation and clearance remain poorly understood, which is critical for developing potential therapeutic interventions. Here, we employed TIRFM, superresolution microscopy, and single-molecule photobleaching techniques to investigate the isoform-specific effects of apoE on the rate constants of Aβ42 aggregation at the single-fibril level, as well as to quantify the binding affinity and specificity of apoE isoforms to individual Aβ fibril ends. Our results show that apoE4 is ca. 4–5 times less effective than apoE3 and apoE2 in inhibiting fibril elongation, while secondary nucleation is largely unaffected by any of the isoforms. Furthermore, apoE3 exhibits stronger and more specific binding to fibril ends compared to apoE4. These findings suggest that apoE4’s reduced affinity for growing fibril ends may impair microglial clearance and increase amyloid deposition through a higher elongation rate in the brain of ApoE-ε4 carriers.